The prisoner's wife [large type] - Brookes, Maggie (Center Point Large Print, 2020)
"Inspired by a true story, a daring deception plunges a courageous and desperate young woman deep into the horrors of a Nazi POW camp to be with the man she loves. Czechoslovakia, 1944 In the dead of night a farm girl and a British soldier creep through abandoned villages. Izabela and prisoner-of-war Bill have secretly married, and are on the run, searching for Izabela's brother and father, who are fighting the Nazis. The husband and wife have evaded capture in the countryside for a week, but when their luck runs out, they are delivered into the hands of the occupying enemy. But they have prepared for this moment, disguising Izabela as a man. The pair are transported to a POW camp and faced with living conditions far worse than those experienced by any animal on Izabela's farm. They will need the help of their fellow POWs to maintain their deception, and the gravity of the situation becomes chillingly apparent; if they are discovered, Izabela will have put not just herself and Bill in great danger, but also all the men around them. The Prisoner's Wife tells of an incredible risk, and how our deepest bonds are tested in desperate times. Bill and Izabela's is a story of love and survival, against the darkest odds"--Provided by publisher.